Проблеми формування іншомовної компетентності в умовах інклюзії: духовно-ціннісний та педагогічно-методичний виміри - Косенко, А.В.; Беженар, I. В.; Закордонець, Н.І. (My University, 2026)
The article considers the problem of forming ethical and spiritual communication in a foreign language in an inclusive educational environment. The relevance of the study is due to the growing attention to the humanistic values of modern education, the need to ensure equal access to high-quality foreign language learning and the need to develop a linguistic personality capable of empathetic, responsible and value-oriented interaction. The focus of the study is the relationship between language competence, inclusive pedagogy and spiritual intelligence as an integrative characteristic of the personality. The purpose of the article is the theoretical justification and analysis of pedagogical approaches to the formation of ethical and spiritual foreign language communication of students in an inclusive educational process. The study uses methods of theoretical analysis of scientific sources, generalization of pedagogical experience, interdisciplinary synthesis of the provisions of linguistic didactics, inclusive education and spiritually-oriented pedagogy. As a result of the study, the essence of ethical and spiritual communication in a foreign language was determined, its structural components (value-motivational, cognitive, communicative-behavioral) were outlined, and the pedagogical conditions for its formation in an inclusive environment were also identified. It was proven that the integration of spiritual and value content into the process of teaching foreign languages contributes to the development of tolerance, intercultural sensitivity, respect for diversity and awareness of human dignity. The practical significance of the study lies in the possibility of using its results in the professional training of foreign language teachers, the development of inclusive educational programs and teaching and methodological materials aimed at the formation of a holistic linguistic and spiritually mature personality. Research on teaching a foreign language in inclusive conditions has great prospects today, namely, it requires further study of the development of teaching materials and the creation of pedagogical conditions for various categories of people with disabilities.
Keywords: foreign language competence, inclusion, inclusive education, spirituality, foreign language teaching methodology, digital education, spiritual intelligence.